Democracy: Freedom of Speech and Floor-crossing interface - Rahman, Ziaur (Northern University Journal of Law, 2014)
Democracy is a sine qua non for the administration of a modern State. Modern developed countries are trying to flourish the democratic culture in every sphere of their stately actions. The framers of the Constitution of Bangladesh have made many provisions ensuring the true democracy in many Articles of the Constitution. As part of these, Preamble, Articles 7, 9, 11 and 59 deal with the democratic character of the government. On the other hand, Article 39 deals with the freedom of speech. But Article 70 puts a barrier on the exercise of freedom of vote of the Members of Parliament against his party decision. The provisions of Article 70 of the Constitution of Bangladesh are pushing the democracy in a back seat. This provision does not help the Parliament to uphold the democratic values of the Constitution. By this provision, the freedom of speech as enunciated in Article 39 of the Constitution becomes a useless tool in respect of giving vote inside the Parliament. This study seeks to find out the relation among democracy, freedom of speech and floor-crossing, to examine the desirability of the provision of floorcrossing, to explore the bad effects of Article 70 in democratic culture of in Bangladesh and to find out the possible way of solving this problem. DOI: http://dx.doi.org/10.3329/nujl.v1i0.18523 Northern University Journal of Law Vol.1 2010: 24-38